Literasi Budaya Melalui Pembelajaran Seni Rupa Di SD Negeri 2 Sumbang - Rhegita Gandes Pramesti; Lia Mareza; Okto Wijayanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Cultural literacy is an important aspect of basic education to foster understanding and appreciation of Indonesia's cultural diversity from an early age. Fine arts learning is one of the effective means in instilling cultural values to students. This study aims to determine students' cultural literacy through fine arts learning and identify the supporting and inhibiting factors. The method used is qualitative research with a case study approach. Data were collected through observation, interviews, and documentation at SD Negeri 2 Sumbang. The results showed that fine arts learning through hands-on practices, such as making hand-written batik, handicrafts from used goods, and stamping, was able to improve students' understanding of the meaning of culture, visual culture, and local culture-based work skills. The involvement of practitioners from outside the school also enriches students' learning experience and strengthens their identity and pride in the nation's culture. The conclusion of this research is that contextualized and local culture-based fine arts learning is proven effective in fostering students' cultural literacy from an early age.Literasi budaya merupakan aspek penting dalam pendidikan dasar untuk menumbuhkan pemahaman dan penghargaan terhadap keberagaman budaya Indonesia sejak dini. Pembelajaran seni rupa menjadi salah satu sarana yang efektif dalam menanamkan nilai-nilai budaya kepada siswa. Penelitian ini bertujuan untuk mengetahui literasi budaya siswa melalui pembelajaran seni rupa serta mengidentifikasi faktor pendukung dan penghambatnya. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi di SD Negeri 2 Sumbang. Hasil penelitian menunjukkan bahwa pembelajaran seni rupa yang dilaksanakan melalui praktik langsung, seperti pembuatan batik tulis, kerajinan dari barang bekas, dan cap, mampu meningkatkan pemahaman siswa terhadap makna budaya, visual budaya, dan keterampilan berkarya berbasis budaya lokal. Keterlibatan praktisi dari luar sekolah turut memperkaya pengalaman belajar siswa dan memperkuat identitas serta rasa bangga terhadap budaya bangsa. Simpulan dari penelitian ini adalah pembelajaran seni rupa yang kontekstual dan berbasis budaya lokal terbukti efektif dalam menumbuhkan literasi budaya siswa sejak usia dini.